2019
DOI: 10.12669/pjms.35.6.377
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipoprotein (a) levels in acute coronary syndrome; Comparison of younger and elderly patients with healthy controls

Abstract: Objective: To compare and see the association of serum Lipoprotein (a) levels in younger and older patients suffering from acute coronary syndrome compared to healthy controls Methods: This case control study was conducted in department of cardiology, King Edward Medical University, Lahore from January to December 2015. Total 180 subjects (90 cases and 90 healthy controls, subdivided in 45 young and old in each group ≤/>45 years of age) were included in the study by non-probability purposive sampling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…The median Lp(a) level in the present study was 20.75 mg/dL. Previously, higher mean levels were observed for those with acute coronary syndrome (47.03 mg/dL, n=90) and diabetics (47.65 mg/dL, n=68) 24,25 . These levels were slightly higher than those observed in the Southeast Asian population (Figure 4) 26 .…”
Section: Discussioncontrasting
confidence: 47%
“…The median Lp(a) level in the present study was 20.75 mg/dL. Previously, higher mean levels were observed for those with acute coronary syndrome (47.03 mg/dL, n=90) and diabetics (47.65 mg/dL, n=68) 24,25 . These levels were slightly higher than those observed in the Southeast Asian population (Figure 4) 26 .…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies [ 21 ] pointed out that the higher the level of HCY, the greater the risk of cardiovascular diseases. Lp-a, as a protein complex synthesized in the liver, can prevent blood clot dissolution in blood by combining with fibrin, which is the main cause of atherosclerosis [ 22 ]. TNF- α and hsCRP both belong to inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that aimed to analyse the association between Lp(a) levels and ACS in younger and older patients, Hanif et al, concluded that in patients younger than 45 years, serum Lp(a) (>30 nmol/L) is strongly associated with AMI [ 83 ].…”
Section: Resultsmentioning
confidence: 99%